2015
DOI: 10.1590/1809-9823.2015.14006
|View full text |Cite
|
Sign up to set email alerts
|

Imagem corporal, humor e qualidade de vida

Abstract: ResumoObjetivo: Caracterizar, quanto a imagem corporal, humor e qualidade de vida, mulheres pós-menopáusicas que buscam atendimento de fisioterapia dermatofuncional, dermatologia e medicina estética. Materiais e Métodos: Estudo transversal com 46 mulheres que buscaram atendimento estético em três locais na cidade de Porto Alegre-RS, Brasil. Foram coletados dados sociodemográficos e de saúde. Foram aplicados os instrumentos: Escala de Depressão Geriátrica (GDS-15), questionário de qualidade de vida WHOQOL-bref … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 11 publications
3
10
0
14
Order By: Relevance
“…As important as nutritional status is the relationship the elderly persons maintain with their body and their quality of life, which, in the present study, was also found to be a relevant outcome and one of the predictors of body image satisfaction, as the better the quality of life scale score, the greater the chance of being satisfied. Like the present study, Skopinski et al 28 also found a better quality of life among those who were satisfied with their body image in a study of 46 postmenopausal women, most of whom were young. It was observed that the greater the disbody image satisfaction, the worse the quality of life perceived in the "physical", "psychological" and "environment" domains of the Whoqol-bref, another instrument that measures quality of life.…”
Section: Discussionsupporting
confidence: 78%
“…As important as nutritional status is the relationship the elderly persons maintain with their body and their quality of life, which, in the present study, was also found to be a relevant outcome and one of the predictors of body image satisfaction, as the better the quality of life scale score, the greater the chance of being satisfied. Like the present study, Skopinski et al 28 also found a better quality of life among those who were satisfied with their body image in a study of 46 postmenopausal women, most of whom were young. It was observed that the greater the disbody image satisfaction, the worse the quality of life perceived in the "physical", "psychological" and "environment" domains of the Whoqol-bref, another instrument that measures quality of life.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies that address issues related to body image (25) and body and mind integration (26) have identified the association of these aspects with the physical and environmental domains of quality of life. These results corroborate the discussion of the findings of the present study since the proposed intervention was based both on a body-focused approach (physical and subjective) and on a perspective of integrating emotions, feelings and actions.…”
Section: Resultsmentioning
confidence: 99%
“…The self-perception that the elderly has in relation to your body is important because it impacts on body image [22]. In Table 2 it is possible to infer that the variables of greater influence with regard to dissatisfaction in relation to body image are: body fat mass and the waist, hip relationship, because changes in these variables are visible to the naked eye and are usually associated with excess weight.…”
Section: Discussionmentioning
confidence: 99%